(untitled) (Archive of Conferences, 2021)
The main task of the younger generation is to become competent citizens of the country where they were born and bred. Clearly, the formation of youth culture on the basis of the requirements of the time and epoch, first of all, is to reflect the purposefulness and professional orientation of young people in the construction of the state and society and the correct definition of their future life.